2005
DOI: 10.1597/03-045.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alveolar Bone Grafting: A Survey of ACPA Teams

Abstract: There is wide acceptance of secondary bone grafting and there is a consensus for the age of grafting (6 to 9 years) and donor site (iliac crest). The disturbing finding was the lack of postoperative x-ray evaluation of the results. With so much variability in management, the use of a routine, standardized scale to measure postoperative results would allow for better outcome studies in alveolar bone grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
59
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 13 publications
5
59
0
1
Order By: Relevance
“…In recent years, consensus has coalesced around secondary alveolar bone grafting as the preferred treatment at some 90 percent of centers. 15 In contrast, primary alveolar bone grafting, undertaken in the infant at the time of cleft palate repair, is now seldom performed, as it has been associated with subsequent impairment in maxillary growth. 16,17 Primary gingivoperiosteoplasty is an alternative approach also performed in the first year of life that does not rely on bone grafting but rather uses local mucoperiosteal flaps to close the alveolar defect.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, consensus has coalesced around secondary alveolar bone grafting as the preferred treatment at some 90 percent of centers. 15 In contrast, primary alveolar bone grafting, undertaken in the infant at the time of cleft palate repair, is now seldom performed, as it has been associated with subsequent impairment in maxillary growth. 16,17 Primary gingivoperiosteoplasty is an alternative approach also performed in the first year of life that does not rely on bone grafting but rather uses local mucoperiosteal flaps to close the alveolar defect.…”
Section: Discussionmentioning
confidence: 99%
“…25 Some centers, however, do perform gingivoperiosteoplasty to achieve early union of the dentoalveolar arch and possibly reduce the need for later bone grafting. Surgery at the alveolar cleft site has the potential to disrupt facial development.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with prior studies that have reported the iliac crest to be most popular bone graft source. 10,22 Approximately 2% had bone from the femur, tibia, or ribs. None of the patients had bone grafts from the cranial bones.…”
Section: Discussionmentioning
confidence: 99%